The Effect of Organic Fertilizer and Age of Defoliation of Some Substance Nutrition Elephant Grass Silage (Pennisetum Purpureum) - Syamsuddin, . (Buletin Nutrisi dan Makanan Ternak, 2013)
An experiment was conducted to investigate the effects of organic fertilizer and age defoliation of some nutrients silage elephant grass (Pennisetum purpureum). This experiment used elephant grass, compost, and organic liquid fertilizer. The experiment was conducted according to completely randomized design pattern 3 x 3 factorial with 3 replications, the first factor is fertilization: A1 (without fertilizer), A2 (fertilizing with compost) and A3 (fertilizing with a liquid fertilizer), while the second factor is the age of defoliation: B1 (age defoliation 30 days), B2 (age defoliation 45 days) and B3 (age defoliation 60 days). The results showed that the crude protein content of elephant grass silage at the age of 30 days defoliation treatment is higher than the age of defoliation 45 days and 60 days. While the highest crude fiber obtained at the age of defoliation 60 days. Elephant grass defoliation at the age 45 days and compost can to improve the content of crude fat and BETN elephant grass silage.